Rpb7 subunit of RNA polymerase II interacts with an RNA-binding protein involved in processing of transcripts - Mitsuzawa, Hiroshi (Oxford University Press, 2003)
Rpb4–Rpb7, a dissociable subcomplex of RNA polymerase II (pol II), is required for transcription initiation. To understand the role of Rpb7 in transcription initiation or other processes in transcription, we carried out a two-hybrid screen for proteins that interact with Rpb7 of the fission yeast Schizosaccharomyces pombe. The screen identified the S.pombe homolog of the Saccharomyces cerevisiae Nrd1, an RNA-binding protein implicated in 3′ end formation of small nucleolar and small nuclear RNAs transcribed by pol II. The S.pombe protein, named Seb1 for seven binding, was essential for cell viability, and bound directly to Rpb7 in vitro. Saccharomyces cerevisiae Rpb7 also interacted with Nrd1, indicating that the interaction is conserved in evolution. Glu166 and/or Asp167 of S.pombe Rpb7, residues near the C-terminus of the 172 amino acid protein, were found to be important for its interaction with Seb1. Our results suggest that Rpb7 may function to anchor a processing factor to the pol II apparatus, thereby coupling RNA processing to transcription. The role for Rpb7 is consistent with its location in the pol II complex determined by recent structural studies.